Berlin Workshop Series 2006 : Equity and Development - Kochendörfer-Lucius, Gudrun (Washington, DC : World Bank, 2012)
This year, the workshop examined the conceptual foundation of the workshop sessions by discussing the definition of equity itself. What do we mean by equity, and how does equity differ from equality? Whereas equity is commonly associated positively with impartiality and justice, economists understand equality as an idealistic and unattainable goal often linked to socialism and communism. The terminological twins equity/equality, however, can be conceptualized in highly diverging ways with different consequences for development strategy. The discussions throughout the workshop mirror the controversial positions of international discourse on the topic. Through the varying dimensions of these terms, discussions focused on the different responsibilities for political action such terms entail. For example, whereas equality in outcome implies an egalitarian perspective, economic studies on inequality in outcome mostly take into account the results of actions and conditions such as unequal incomes. Session I, on what is equity, and, what is the role for governments in the promotion of equity, further discussed how does this role differ between developed and developing countries. Nonetheless, it was suggested that before operationalizing and measuring inequity, the concept itself has to be clarified, and, further arguments indicated that one future challenge for development policy is precisely to combine growth-promoting policies with policies that assure that the poor can fully participate in the opportunities that growth offers. Session II, on equity-enhancing social transformation and historical evidence from European and Transition Countries, focus on policies that impact equity. Session III, on building efficient welfare states and lessons learnt, discussed the task of formulating policies that foster both efficiency and equitable social welfare, while Session IV, on international inequalities and what can be done to reduce them, focuses on the global level, contrary to Session III which concentrated on equity issues at the national level. Finally, Session V, on what will greater integration mean for inequalities between and within the richer and poorer countries of the New Europe, draws a very differentiated picture. Conclusions outlined key issues that need to be addressed, noting the importance of carefully analyzing different redistributive instruments with respect to their effects on growth and efficiency, and vice versa.